Repair bond strength and degradation of glass ionomer cements after mechanical and chemical challenges - Leandro Rahal Mestrener; Sandra Rahal Mestrener; Cleidiel Aparecido Araujo Lemos; André Luiz Fraga Briso; Renato Herman Sundfeld; Ticiane Cestari Fagundes (Universidade Estadual de Campinas, 2020)
Aim: Little is known about the reparability of glass ionomer cements (GICs) after storage in acid environments. The aim of this study was to evaluate the solubility and repairability of GICs immersed in acid solutions and subjected to brushing. Methods: Thirty discs of each GIC (Vitremer, VitroFil LC, VitroFil, and Maxxion R) were divided into three immersion groups: distilled water, Coca-Cola, or hydrochloric acid (HCl), then subjected to brushing. The weight of discs was measured before and after the immersions to determine mass alteration. Each disc was repaired, by adding the same brand of GIC over its surface. After immersing the repaired specimens in same solutions, shear bond strengths using universal testing machine were measured. Two-way ANOVA and Tukey's test was used (α=0.05). Results: Resin-modified GICs degrade after HCl immersion followed by brushing (p<0.05), while self-cured GICs were negatively affected by all challenges (p<0.05). The challenges decreased the repair strength for VitroFil LC (p<0.05), which had higher repair shear bond strength than the other GICs (p<0.05), exhibiting most cohesive failures. Conclusion: Self-cured GICs degraded when immersed in all acid solutions with brushing while resin-modified GICs only degraded following HCl immersion with brushing. Despite exhibiting the best repair results, VitroFil LC was the only GIC that was influenced by all the acid challenges.